Politik Dinasti dan Regresi Demokrasi di Indonesia: Analisis Pelantikan Gibran Rakabuming Raka dalam Perspektif Maslahah Mursalah - Sugitanata, Arif; Arif Sugitanata; Rizal Al Hamid (IAIN Metro, 2025)
The phenomenon of dynastic politics has been strengthening within Indonesia’s political dynamics following the Constitutional Court’s Decision No. 33/PUU-XIII/2015, which opened opportunities for the families of officials to run for elections. This phenomenon reached its peak in the 2024 General Election when Gibran Rakabuming Raka, the son of President Joko Widodo, was elected as Vice President after a sudden revision of the age requirement for candidates through Constitutional Court Decision No. 90/PUU-XXI/2023. This study aims to analyze Gibran’s inauguration within the context of dynastic politics and its impact on democratic regression in Indonesia. It employs Maslahah Mursalah as an analytical framework to assess the balance between benefits (maslahah) and negative consequences (mudarat). The research adopts a qualitative approach with a descriptive-analytical-exploratory nature, relying on a literature-based study. The findings indicate that Gibran’s inauguration reflects the strengthening of dynastic politics, which undermines the checks and balances mechanism in Indonesia’s democracy. The legal decision enabling his candidacy reveals judicial co-optation, eroding public trust in the Constitutional Court’s independence and narrowing the space for fair political competition. From the perspective of Maslahah Mursalah, the claimed benefits—such as leadership continuity and political stability—are outweighed by greater negative consequences, including the reinforcement of political oligarchy and the erosion of the rule of law. These findings affirm that dynastic politics has the potential to harm democracy by restricting access to leadership based on meritocracy. Therefore, legal and policy reforms are necessary to limit dynastic politics in order to safeguard the integrity of democracy in Indonesia.